Risk Analysis of the Supply Chain of Building Project Construction Materials (Hasna Medika Majalengka Heart Clinic) - Dwi Nah Vasa; Nada Azharul Jannah; Bayu Nugraha; Lutfi Marantica (Riviera Publishing, 2026)
This research aims to analyze risks in the construction material supply chain to ensure the efficiency and success of the project. The study focuses on the strategic project for the construction of the Hasna Medika Heart Clinic Building in Majalengka, where the dependence on material availability and supply chain complexity makes risk management crucial to prevent delays and cost overruns. The research methods used are a mixture of qualitative and quantitative, including field observations, interviews, and preliminary and main surveys to seven and ten expert respondents from contractors and suppliers. Data are analyzed to identify and assess the frequency of risk emergence. The results of the study identified 18 risk variables. The analysis shows differences in antara_kontraktor_dan_supplier perceptions of the most sering_terjadi risiko_yang. The contractor noted the main risk on the change of order (A2, 27.78%), additional requests from the owner (A5, 25.93%), and increases in material prices (A16, 27.78%). Meanwhile, suppliers are more concerned about inaccurate schedules from contractors (A1, 25.93%) and delivery delays due to payment problems (A9, 25.93%). However, both sides reached consensus on two of the most critical risks that are equally frequent, namely ineffective communication (A12) and rising material prices (A16). In conclusion, effective communication and price fluctuation management are the key priorities for mitigating supply chain risks in construction projects, and contractors and suppliers should establish transparent coordination mechanisms and adaptive budget planning to prevent delays and cost overruns.